THE URGENCY OF GOVERNMENT AUTHORITY IN PROCUREMENT OF LAND FOR DEVELOPMENT FOR THE PUBLIC INTEREST WITH PANCASILA JUSTICE - Achmad, Sri Yanti; Mashari, Mashari (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to describe the Government's authority in land acquisition for development for the public interest. In this study, it is related to theAvailability land for development for the public interest has not been fair in Pancasila. The problem in this study is about the urgency of the government's authority in procuring land for development for the public interest based on Pancasila justice. The research method used in this study is a normative juridical approach, which is a study that uses secondary data as the main data, while primary data as supporting data. The results of this study show that Settings land for development in the public interest carried out by the Government by revoking land rights based on the Job Creation Law to try to harmonize the arrangements in the Law Number 2 of 2012 concerning Procurement Soil For Development for the public interest with its implementation regulations. The results of the study on pAvailability land for development in the public interest has not been fair to Pancasila, this is influenced by internal factors, namely the determination of compensation is not carried out optimally. External factors, namely disputes arising in the acquisition of land owned by the community affected by infrastructure development projects, generally cause conflicts, contradictions, and disagreements regarding the amount of compensation. The urgency of the Government's authority in procuring land for development in the public interest which is fair to Pancasila by upholding basic principles including humanity and justice based on Pancasila so that it does not cause losses to parties who have lost their land rights